Analysis of the influence of entrepreneurial behavior on business performance - Sastra, Dian; Raysharie, Puput Iswandyah; Benius, Benius; Giopingki, Erwin; Heldo, Heldi; Reyna, Laura; Sirait, Adelia; Simandalahi, Lusiana; Cahnia, Murny; Azzahra, Nadya; Mawardani, Rizka (Journal Magister Ilmu Ekonomi Universtas Palangka Raya : GROWTH, 2024)
This scholarly investigation is specifically designed to thoroughly explore and analyze the multifaceted influence exerted by entrepreneurial behavior on the overall performance of businesses across various sectors. By engaging in a comprehensive literature review, this research endeavors to construct an intricate and nuanced understanding of the ways in which entrepreneurial behavior can effectively shape, mold, and influence a diverse array of dimensions related to business performance, including profitability, market share, and customer satisfaction. In this academic discourse, the research delineates the principal findings derived from a meticulous examination of related literature, with a focused emphasis on identifying the pivotal factors that serve to mediate and facilitate the correlation between entrepreneurial behavior and the resultant business performance outcomes. The abstract conclusions drawn from this investigation can serve as a foundational basis for subsequent research endeavors aimed at further elucidating this critical relationship. The empirical results generated through this rigorous research methodology indicate a significant positive correlation between entrepreneurial behavior and enhanced business performance, underscoring the importance of proactive entrepreneurial initiatives. Specifically, initiatives designed to uncover and capitalize on new business opportunities, coupled with innovative approaches to marketing strategies and a prudent capacity for risk management, all contribute fundamentally to the enhancement of business productivity and long-term sustainability. This research ultimately provides profound and comprehensive insights that are invaluable for business stakeholders, including entrepreneurs, investors, and policymakers, thereby equipping them with the knowledge necessary to navigate the complexities of the entrepreneurial landscape effectively.